Transcendental Communication in Sufism: Exploring the Spiritual Relationship Between Human Beings and God - Gema Mustika Idaman (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
ABSTRACTIn the development of communication science, attention to spiritual and transcendental dimensions is still relatively minimal. This study aims to explore the meaning and process of transcendental communication between humans and God from a Sufism perspective. Transcendental communication is understood as a form of vertical and spiritual inner interaction, in which humans try to unite with the will of God through spiritual practices such as dhikr, prayer, meditation, and contemplation. Using a qualitative-descriptive approach and literature review, this article describes how Sufism interprets the relationship between humans and the Creator as a process of cleansing the soul (tazkiyatun nafs) which culminates in the experience of fana (melting into God) and baqa (eternity in Divine consciousness). This communication is not only symbolic or verbal, but also touches the deepest dimensions of feeling and spiritual awareness. The results of this study indicate that Sufism provides a rich spiritual foundation in understanding transcendental communication, and offers solutions to the spiritual crisis experienced by modern humans.Keywords: transcendental communication, Sufism, spiritual relations, dhikr, fana.